The Synthesis and Bioactivity Study of Anthraquinones, And the Isolation of Bioactive Compounds from Leea Indica (Burm.F.) Merr. - Saha, Koushik (2005)
Damnacanthal and nordamnacanthal were synthesized due to their interesting property as cytotoxic agents against several cancer cell-lines. Friedel-Craft condensation reaction has been used to prepare anthraquinone back-bone in view of its less stringent requirements with regards to reaction conditions (such as humidity), highly reactive reagents and lower cost. Various other synthetic methods were used to prepare their derivatives. A total 43 derivatives of anthraquinone have been successfully synthesized including damnacanthal and nordamnacanthal. A new rearrangement was observed when phthalic anhydride reacted with different halophenols leading to a few rearrangement products depending on the types of halophenol used. All the synthesized compounds were subjected to cytotoxicity assay against different cancer cell lines and antioxidant activities. A total 22 anthraquinone derivatives showed the cytotoxicity against the cell-lines used. Among the compounds, 2-bromomethyl-l,3-dimethoxyanthraquinone (A-34) was found as most cytotoxic against all the cell-lines. 3-Acetoxy-2-bromomethyl-1- methoxyanthraquinone (A-42) and damnacanthal (A-46) also showed strong cytotoxicity against different cancer cell-lines. On the other hand, only two synthesized anthraquinones, damnacanthal (A-46) and nordamnacanthal (A-37) showed strong antioxidant activity comparable with vitamin E. A preliminary antioxidant and nitric oxide inhibition activities screening of seven medicinal plants including Lasianthus oblongus, Psychotria rostrata, Spermacoce exilis, Chasalia chartacea, Hedyotis verticillata, Spermacoce articularis and Leea indica have been conducted properly. Leea indica (family: Leeaceae) has been selected for further investigation. Phytochemical study on this plant has resulted the isolation of a novel carotenoid, leeatene (L-7) and nine other known compounds including squalene (L- 1), hexadecanoyl-0-amyrin (L-2), vitamin E (L-3), 1 - tetratriacontanol (L-4), P-amyrin (L-5), 3-hydroxy-12-oleanen-28-oic acid (L-6), Psitosteryl- P-D-glucopyranoside (L-8), 2a,3a,23-trihydroxy-12-oleanen-28-oiacc id (L-9) and phloridzin (L-10). The chemical structure of the compounds was established based on spectral studies including ultraviolet-visible, infrared, one and two dimensional nuclear magnetic resonance and mass spectroscopies. All isolated compounds were tested for their antioxidant and cytotoxic activities. Three compounds including vitamin E (L-3), leeatene (L-7) and phloridzin (L-10) showed antioxidant activity whereas squalene (L-1), hexadecanoyl-P-arnyrin (L-2), 1- tetratriacontanol (L-4), 3-hydroxy- 12-oleanen-28-oic acid (L-6), leeatene (L-7), Psitosteryl- P-D-glucopyranoside (L-8), 2a,3a,23-trihydroxy-12-oleanen-28-oica cid (L-9) were found cytotoxic against different cancer cell lines.